Nanometer hydrated calcium silicate with adjustable setting time as well as preparation method and application of nanometer hydrated calcium silicate
By introducing zinc ions and polycarboxylic acid reduction agents in the nano -hydrophilic acid silicate system, regulating zinc and silicon comparisons, preparing calcium -hydraulic silicate with adjustable condensation time, solving the existing material early strong effect The problem realizes the controllability of concrete strength and coagulation time.
Patent Information
- Application Number
- CN202411261884.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2025-01-24
AI Technical Summary
The existing nano-hydrated calcium silicate materials have fast early strength, resulting in short settling time of concrete and large loss of working performance, and the strength still needs to be further improved.
By introducing zinc ions in the system, zinc and silicon comparison, combined with polycarboxylic acid water reduction agents and stabilizers, nano hydrophic silicate with adjustable coagulation time is prepared.
The concrete condensation time is regulated according to engineering needs, which significantly improves the early and middle and late stages of cement base materials and high stability. It is suitable for the preparation of various cement base materials.
Smart Images

Figure CN119349917A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building material admixtures, and in particular to nano calcium silicate hydrate with adjustable setting time, and a preparation method and application thereof. Background Art
[0002] Cement-based materials are one of the important materials widely used in construction projects. In the manufacture of traditional cement-based materials, steam curing is required to improve the early strength of concrete. However, steam curing consumes a lot of heat energy, which increases production costs. It is also easy to emit greenhouse gases and pollutants, causing environmental pollution, and it is very easy to cause "thermal damage" to concrete, reducing the durability of concrete. In engineering, early strength agents are often used to accelerate the early hydration rate of cement-based materials to improve the early strength of concrete. However, the addition of traditional early strength agents often sacrifices the later strength of concrete to improve its early strength, and it is easy to cause many negative effects. For example, the dosage of triethanolamine early strength agents is difficult to control, and excessive dosage can easily lead to super slow setting; chlorine-containing early strength agents can easily cause steel corrosion; sulfate early strength agents can easily reduce the impermeability and corrosion resistance of concrete, resulting in poor durability of concrete.
[0003] In recent years, the development of nanotechnology has provided a new way to improve the performance of cement-based materials. Nano-calcium silicate hydrate (CSH) in nanocrystalline early strength agents is itself the core product of silicate cement hydration. After being added to concrete, it can more quickly improve the early strength and improve the microstructure of cement-based materials without introducing harmful substances. At the same time, as one of the main products of cement cementitious system, nano-calcium silicate hydrate has an important influence on the strength and stability of cement-based materials. Many studies have shown that the addition of nano-calcium silicate hydrate can significantly improve the early strength of concrete, which has a huge driving force for the realization of less steaming and fast demolding of prefabricated components. However, due to the rapid early strength effect of nano-calcium silicate hydrate, the setting time of concrete is significantly advanced, and the working performance of concrete is greatly lost, resulting in the application scenarios of nano-calcium silicate hydrate being limited.
[0004] Chinese patent CN112010581B "A hydrated calcium silicate nanocrystalline core suspension and its preparation method" discloses a hydrated calcium silicate nanocrystalline core suspension, which can be transformed into dicalcium silicate with high hydration activity by doping siliceous solid waste with waste concrete powder and metal ions and then calcining; a large amount of hydrated calcium silicate is quickly formed when it meets water, and under alkaline conditions, the dispersion effect of polycarboxylate water reducer can significantly reduce the size of the hydrated calcium silicate nanocrystalline core, and improve the early strength and mid-to-late strength of cement-based materials. However, its early strength effect is fast, resulting in a short setting time of concrete, a large loss of working performance, and the strength still needs to be further improved.
[0005] Therefore, it is of great significance to provide a nano calcium silicate hydrate and a preparation method thereof that can adjust the setting time of concrete, improve the working performance of concrete, and further improve its strength. Summary of the invention
[0006] In view of the fact that the existing nano calcium silicate hydrate materials have a fast early strength effect, resulting in a short setting time of concrete, a large loss of work performance, and the strength still needs to be further improved, the present invention provides a nano calcium silicate hydrate with adjustable setting time and its preparation method and application, which can not only improve the early strength of cement-based materials, but also can adjust the setting time of concrete according to actual engineering needs to meet different engineering needs. The product has high stability, is easy to store, is suitable for various cement-based materials, and is of great significance for the improvement and promotion of existing building material production processes.
[0007] To achieve the above object, the technical solution adopted by the present invention is:
[0008] A method for preparing nano calcium silicate hydrate with adjustable setting time, comprising the following components by weight:
[0009] 10-40 parts of calcium source, 0.5-3 parts of zinc source, 10-30 parts of silicon source, 5-15 parts of polycarboxylic acid water reducer, 0.5-2 parts of stabilizer, and 100-400 parts of water.
[0010] Furthermore, the calcium source is one or more of calcium acetate, calcium nitrate, calcium formate and calcium chloride.
[0011] Furthermore, the silicon source is a soluble silicon salt.
[0012] Furthermore, the silicon source includes one or more of sodium silicate, potassium silicate, sodium metasilicate, and potassium metasilicate.
[0013] Furthermore, the zinc source is one or more of zinc acetate, zinc nitrate, zinc formate and zinc chloride.
[0014] Furthermore, the water reduction rate of the polycarboxylic acid-based water reducer is ≥35%.
[0015] Furthermore, the stabilizer is one or more of block polyether F68, povidone K30, sodium dodecyl sulfate, and sodium dodecyl sulfonate.
[0016] Another object of the present invention is to provide a method for preparing nano calcium silicate hydrate with adjustable setting time.
[0017] A method for preparing nano calcium silicate hydrate with adjustable setting time according to any of the above items, comprising the following steps:
[0018] S1. Preparation of a dropping solution: Weigh a calcium source, a zinc source and a silicon source, respectively, and dissolve them in water to obtain a calcium source dropping solution, a zinc source dropping solution and a silicon source dropping solution;
[0019] S2. Preparation of a base liquid: mixing a polycarboxylate water reducer, a stabilizer and water to obtain a base liquid, and placing it in a cold water bath;
[0020] S3. Preparation of nano-hydrated calcium silicate: adding the calcium source droplet, zinc source droplet and silicon source droplet to the base liquid, stirring and adjusting the pH value to 10-13 to obtain nano-hydrated calcium silicate.
[0021] Furthermore, the temperature of the cold water bath in S2 is 5-15°C.
[0022] Furthermore, the addition time of the calcium source droplet, zinc source droplet and silicon source droplet in S3 is 2-3h; the stirring speed is 5000-10000r / min, and the time is 3-5h; the pH value is adjusted by NaOH and HNO3.
[0023] Furthermore, the mass concentration of the nano-hydrated calcium silicate is 20-25%, and the median particle size is 100-200 nm.
[0024] Another object of the present invention is to provide an application of nano calcium silicate hydrate with adjustable setting time.
[0025] Application of the above-mentioned nano calcium silicate hydrate with adjustable setting time in the preparation of concrete.
[0026] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0027] (1) Compared with the existing nano calcium silicate hydrate synthesis process, the nano calcium silicate hydrate with adjustable setting time prepared by the present invention introduces zinc ions into the system. By adjusting the zinc-silicon ratio, the setting time of concrete can be orderly adjusted according to the actual needs of the project, showing stronger adaptability. In engineering, this controllable strength adjustment can meet the different requirements of different projects for the performance of cement-based materials, and can be widely used in the preparation of various cement-based materials, such as concrete, mortar, blocks, etc. By selecting a suitable zinc-silicon ratio, engineers can optimize the performance of materials according to specific project requirements and improve the construction efficiency of the project. For example, in projects such as highways and bridges that have high requirements for early strength, a formula with a relatively low zinc-silicon ratio can be used to ensure that sufficient strength is obtained in a relatively short time. In other projects that require a longer setting time or do not require excessively high early strength, a formula with a relatively large zinc-silicon ratio can be used to obtain more construction time while ensuring strength. Moreover, the nanocrystalline nucleating agent synthesized by the present invention will not have a negative impact on the compressive strength of concrete, can significantly improve the 1d and 3d early strength of cement, and has no effect on the 28d strength. There is no phenomenon of late strength shrinkage, and will not have a negative impact on the mechanical properties and durability of concrete.
[0028] (2) Compared with the traditional nanocrystalline core synthesis process, the present invention simultaneously introduces a polycarboxylic acid-based water-reducing agent and a stabilizer into the nano-calcium silicate hydrate system. The polycarboxylic acid-based water-reducing agent has an extremely high water-reducing rate and dispersion effect. The electrostatic repulsion effect of its molecules can be used to hinder the agglomeration of nano-calcium silicate hydrate crystal cores, so that the nano-calcium silicate hydrate crystal cores are better dispersed in water; and the stabilizer is connected to the surface of the crystal core through a complexing effect, which helps to improve the stability of the crystal core without precipitation. Compared with the traditional crystal core early strength agent, the stability time can be extended by 30-60 days. The two work synergistically to prepare nano-crystalline core particles with small size and good stability. The smaller nano-calcium silicate hydrate crystal core has a stronger hydration effect on cement-based materials, and its excellent stability can enable it to continue to act, thereby significantly improving the early strength and mid-to-late strength of cement-based materials.
[0029] (3) The nano calcium silicate hydrate with adjustable setting time obtained by the present invention has a small crystal nucleus size, high stability, and good early strength effect, and can be directly used to prepare concrete or other cement-based materials. The raw materials are easily available, the preparation method is simple, the synthesis efficiency is high, the reaction conditions are mild, and the production cost can be significantly reduced. It is suitable for large-scale promotion and industrial production, and shows significant environmental benefits and economic value, which is of positive significance for promoting the sustainable development of the construction industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The invention is further described using the accompanying drawings, but the embodiments in the accompanying drawings do not constitute any limitation to the invention. A person skilled in the art can obtain other drawings based on the following drawings without creative work.
[0031] Figure 1 This is a particle size distribution diagram of nano calcium silicate hydrate with adjustable setting time prepared in the examples of the present application. DETAILED DESCRIPTION
[0032] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention is further described by the following examples. Obviously, the following examples are only part of the embodiments of the present invention, rather than all the embodiments; it should be understood that the embodiments of the present invention are only used to illustrate the technical effects of the present invention, rather than to limit the scope of protection of the present invention.
[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0034] The raw materials in the examples can all be obtained commercially; unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0035] Example 1
[0036] A method for preparing nano calcium silicate hydrate with adjustable setting time comprises the following steps:
[0037] S1: preparing a dropping solution: weighing 15 parts of calcium nitrate, 0.5 parts of zinc nitrate and 10 parts of sodium silicate respectively, dissolving them in 40 parts of water respectively, to obtain a calcium source dropping solution, a zinc source dropping solution and a silicon source dropping solution;
[0038] S2: Prepare the base liquid: mix 6 parts of polycarboxylate water reducer, 1 part of block polyether F68 and 40 parts of water to obtain the base liquid, and place it in a cold water bath at 5°C;
[0039] S3: Preparation of nano calcium silicate hydrate: adding the calcium source droplet, zinc source droplet and silicon source droplet to the base liquid for 2 hours, stirring at 6000 r / min for 4 hours, adjusting the pH value to 13 with NaOH and HNO3, and obtaining the nano calcium silicate hydrate with adjustable coagulation time.
[0040] Example 2
[0041] A method for preparing nano calcium silicate hydrate with adjustable setting time comprises the following steps:
[0042] S1: preparing a dropping solution: weighing 15 parts of calcium nitrate, 0.75 parts of zinc nitrate and 10 parts of sodium silicate respectively, dissolving them in 40 parts of water respectively, to obtain a calcium source dropping solution, a zinc source dropping solution and a silicon source dropping solution;
[0043] S2: Prepare base solution: Mix 8 parts of polycarboxylate water reducer, 1 part of povidone K30 and 40 parts of water to obtain base solution, and place in a cold water bath at 5°C;
[0044] S3: Preparation of nano calcium silicate hydrate: adding the calcium source droplet, zinc source droplet and silicon source droplet to the base liquid for 2 hours, stirring at 7000 r / min for 4 hours, adjusting the pH value to 10 with NaOH and HNO3, and obtaining the nano calcium silicate hydrate with adjustable coagulation time.
[0045] Example 3
[0046] A method for preparing nano calcium silicate hydrate with adjustable setting time comprises the following steps:
[0047] S1: preparing a dropping solution: weighing 15 parts of calcium nitrate, 3 parts of zinc nitrate and 10 parts of sodium silicate respectively, dissolving them in 40 parts of water respectively, to obtain a calcium source dropping solution, a zinc source dropping solution and a silicon source dropping solution;
[0048] S2: Prepare base liquid: mix 10 parts of polycarboxylate water reducer, 1 part of sodium dodecyl sulfate and 40 parts of water to obtain base liquid, and place it in a cold water bath at 10°C;
[0049] S3: Preparation of nano calcium silicate hydrate: adding the calcium source droplet, zinc source droplet and silicon source droplet to the base liquid for 2 hours, stirring at 7000 r / min for 5 hours, adjusting the pH value to 12 with NaOH and HNO3, and obtaining the nano calcium silicate hydrate with adjustable coagulation time.
[0050] Example 4
[0051] A method for preparing nano calcium silicate hydrate with adjustable setting time comprises the following steps:
[0052] S1: preparing a dropping solution: weighing 15 parts of calcium nitrate, 1.5 parts of zinc nitrate and 10 parts of sodium silicate respectively, dissolving them in 40 parts of water respectively, to obtain a calcium source dropping solution, a zinc source dropping solution and a silicon source dropping solution;
[0053] S2: Prepare base liquid: mix 10 parts of polycarboxylate water reducer, 1 part of sodium dodecyl sulfate and 40 parts of water to obtain base liquid, and place it in a cold water bath at 15°C;
[0054] S3: Preparation of nano calcium silicate hydrate: adding the calcium source droplet, zinc source droplet and silicon source droplet to the base liquid for 3 hours, stirring at 7000 r / min for 5 hours, adjusting the pH value to 11 with NaOH and HNO3, and obtaining the nano calcium silicate hydrate with adjustable coagulation time.
[0055] Comparative Example 1
[0056] A method for preparing nano calcium silicate hydrate comprises the following steps:
[0057] S1: preparing a dropping solution: weighing 15 parts of calcium nitrate and 10 parts of sodium silicate, respectively, dissolving them in 40 parts of water, respectively, to obtain a calcium source dropping solution and a silicon source dropping solution;
[0058] S2: Prepare the base liquid: mix 6 parts of polycarboxylate water reducer, 1 part of block polyether F68 and 40 parts of water to obtain the base liquid, and place it in a cold water bath at 5°C;
[0059] S3: Preparation of nano calcium silicate hydrate: adding the calcium source droplet and the silicon source droplet to the base liquid for 2 hours, stirring at 6000 r / min for 4 hours, adjusting the pH value to 13 with NaOH and HNO3, and obtaining the nano calcium silicate hydrate.
[0060] Compared with Example 1, the main difference of this comparative example is that no zinc source is added.
[0061] Comparative Example 2
[0062] A method for preparing nano calcium silicate hydrate comprises the following steps:
[0063] S1: preparing a dropping solution: weighing 15 parts of calcium nitrate, 5 parts of zinc nitrate and 10 parts of sodium silicate respectively, dissolving them in 40 parts of water respectively, to obtain a calcium source dropping solution, a zinc source dropping solution and a silicon source dropping solution;
[0064] S2: Prepare the base liquid: mix 6 parts of polycarboxylate water reducer, 1 part of block polyether F68 and 40 parts of water to obtain the base liquid, and place it in a cold water bath at 5°C;
[0065] S3: Preparation of nano calcium silicate hydrate: adding the calcium source droplet, zinc source droplet and silicon source droplet to the base liquid for 2 hours, stirring at 6000 r / min for 4 hours, adjusting the pH value to 13 with NaOH and HNO3, and obtaining the nano calcium silicate hydrate.
[0066] Compared with Example 1, the main difference of this comparative example is that the zinc source is excessive.
[0067] Comparative Example 3
[0068] A method for preparing nano calcium silicate hydrate comprises the following steps:
[0069] S1: preparing a dropping solution: weighing 15 parts of calcium nitrate, 0.5 parts of zinc nitrate and 10 parts of sodium silicate respectively, dissolving them in 40 parts of water respectively, to obtain a calcium source dropping solution, a zinc source dropping solution and a silicon source dropping solution;
[0070] S2: Prepare base solution: Mix 1 part of block polyether F68 with 40 parts of water to obtain base solution, and place in a cold water bath at 5°C;
[0071] S3: Preparation of nano calcium silicate hydrate: adding the calcium source droplet, zinc source droplet and silicon source droplet to the base liquid for 2 hours, stirring at 6000 r / min for 4 hours, adjusting the pH value to 13 with NaOH and HNO3, and obtaining the nano calcium silicate hydrate.
[0072] Compared with Example 1, the main difference of this comparative example is that no polycarboxylic acid water reducing agent is added.
[0073] Comparative Example 4
[0074] A method for preparing nano calcium silicate hydrate comprises the following steps:
[0075] S1: preparing a dropping solution: weighing 15 parts of calcium nitrate, 0.5 parts of zinc nitrate and 10 parts of sodium silicate respectively, dissolving them in 40 parts of water respectively, to obtain a calcium source dropping solution, a zinc source dropping solution and a silicon source dropping solution;
[0076] S2: Prepare base solution: Mix 6 parts of polycarboxylate water reducer with 40 parts of water to obtain base solution, and place in a cold water bath at 5°C;
[0077] S3: Preparation of nano calcium silicate hydrate: adding the calcium source droplet, zinc source droplet and silicon source droplet to the base liquid for 2 hours, stirring at 6000 r / min for 4 hours, adjusting the pH value to 13 with NaOH and HNO3, and obtaining the nano calcium silicate hydrate.
[0078] Compared with Example 1, the main difference of this comparative example is that no stabilizer is added.
[0079] The above embodiments and comparative examples were subjected to performance tests, and the experimental test methods were as follows:
[0080] 1. Test the products of the embodiments and comparative examples.
[0081] 1. Detection method.
[0082] The median particle size of nano-calcium silicate hydrate was measured using a laser particle size analyzer; the setting time of cement paste was tested according to the standard "Test Method for Water Consumption, Setting Time and Stability of Cement Standard Consistency" (GB / T 1346-2011).
[0083] Median particle size: refers to the particle size value that divides the particle size distribution of cement-based materials into two equal parts, that is, the number of particles less than or equal to this particle size is equal to the number of particles greater than this particle size. The median particle size is directly related to the hydration rate and degree of hydration of cement-based materials and the final concrete strength.
[0084] Initial setting time: the time from when cement is mixed with water to when the cement paste begins to lose its plasticity. During this stage, the cement paste gradually loses its fluidity, but still has a certain degree of plasticity. The determination of the initial setting time is of great significance in ensuring that there is enough time for operations such as mixing, transportation, pouring and masonry during the construction process.
[0085] Final setting time: the time from when cement is mixed with water to when the cement paste completely loses its plasticity and begins to have strength. At this stage, the cement paste completely hardens and forms a solid with a certain strength. The determination of the final setting time is of great significance to ensure that the cement can harden as soon as possible after the construction is completed and reach a certain strength, so as to facilitate the next process.
[0086] 2. Test results.
[0087] The appearance, median particle size and cement paste setting time of each group of nano-calcium silicate hydrate are shown in Table 1. The blank group is cement paste without nano-calcium silicate hydrate.
[0088] Table 1 Performance test of nano calcium silicate hydrate of Examples 1-4 and Comparative Examples 1-4
[0089]
[0090] As shown in Table 1, the nano calcium silicate hydrate with adjustable setting time prepared in Examples 1-4 has a relatively uniform appearance, and its specific particle size distribution is as follows: Figure 1 As shown, the median particle size is 100-200nm, which meets the product stability requirements. Comparative Example 3 does not add a polymer dispersant, so the nano calcium silicate hydrate formed is very easy to agglomerate and has poor hydration performance; Comparative Example 4 does not add a stabilizer, and after a short period of storage, the nano calcium silicate hydrate solution has stratification, poor stability, and is difficult to store or use.
[0091] When the zinc-silicon mass ratio is (0.017-0.3):1, the cement paste setting time of Examples 1-4 is shorter than that of the blank group, which has an accelerated setting effect, and the setting time changes with the zinc-silicon ratio. Within a certain range, the amount of silicon remains unchanged. As the proportion of zinc increases, the setting time gradually shortens and then prolongs. When zinc ions are not added to the system, the nano-hydrated calcium silicate prepared in Comparative Example 1 can also significantly shorten the cement paste setting time, but it will cause the problem of strength shrinkage in the later stage; when the zinc addition amount is too high, the nano-hydrated calcium silicate prepared in Comparative Example 2 has a cement paste setting time that is significantly higher than that of the blank group due to the excessive zinc-silicon ratio, which has a significant slow setting effect.
[0092] 2. Test the compressive strength of mortar.
[0093] 1. Detection method: According to the mortar mix ratio shown in Table 2, the nano calcium silicate hydrate in Examples 1-4, Comparative Example 1 and Comparative Example 2 was added, and the nano calcium silicate hydrate was added according to 1.0% of the total mass of the cementitious material. The cement used was P.I42.5 silicate cement.
[0094] Table 2 Mortar mix ratio of Examples 1-4, Comparative Example 1 and Comparative Example 2 (unit / g)
[0095] cement Standard sand Total water volume 450 1350 225
[0096] The compressive strength of the mortar was tested in accordance with GB / T 17671-2021 "Test method for strength of cement mortar", where the blank group was the test group with only mortar added.
[0097] Mortar compressive strength: refers to the maximum pressure that cement-based materials can withstand when subjected to pressure, and is one of the important indicators for measuring material strength.
[0098] 2. Test results: The strength development law of the mortar directly used for the nano-calcium silicate hydrate in Examples 1-4, Comparative Example 1 and Comparative Example 2 is shown in Table 3.
[0099] Table 3 Compressive strength of mortar of nano-hydrated calcium silicate of Examples 1-4 and Comparative Examples 1-2 (MPa)
[0100] serial number Dosage(%) 6h 1d 3d 7d 28d Blank Group 0 0.4 18.4 25.3 43.2 52.2 Example 1 1.0 1.3 28.6 35.6 47.3 55.4 Example 2 1.0 1.5 30.2 37.4 49.2 56.3 Example 3 1.0 0.7 24.5 29.8 44.8 53.1 Example 4 1.0 0.9 26.3 32.5 45.6 53.9 Comparative Example 1 1.0 1.1 27.9 31.8 43.6 50.2 Comparative Example 2 1.0 0 22.7 28.5 38.6 47.2
[0101] In Examples 1-4, when the zinc-silicon mass ratio is (0.017-0.3):1, the nano calcium silicate hydrate has good early strength effect and high stability, and the compressive strength of the mortar at each period is better than that of the blank group.
[0102] When the zinc ion dosage is 0, the nano calcium silicate hydrate obtained in Comparative Example 1 has the best early strength effect, and the 1d mortar compressive strength is 27.9MPa, but there is a phenomenon of later strength shrinkage. The 7d mortar compressive strength and the 28d mortar compressive strength are lower than those of the embodiments, and the 28d mortar compressive strength is even lower than that of the blank group, indicating that the nano calcium silicate hydrate with a zinc ion dosage of 0 will have an adverse effect on the mechanical properties and durability of concrete; when the zinc ion dosage is too high, the nano calcium silicate hydrate prepared in Comparative Example 2 has a greater effect on the strength of concrete, and the early strength 1d mortar compressive strength and 3d mortar compressive strength are far from comparable to those of the embodiments, while the later strength 7d mortar compressive strength and 28d mortar compressive strength are lower than those of the blank group.
[0103] In summary, the present invention introduces zinc ions into the system and adjusts the zinc-silicon ratio, and can orderly adjust the setting time of concrete according to the actual needs of the project, showing stronger adaptability, being able to meet the different requirements of different projects for the performance of cement-based materials, and being widely used in the preparation of various cement-based materials. At the same time, a polycarboxylic acid-based water reducer and a stabilizer are introduced, and the two act synergistically to prepare nanocrystalline core particles with small size and good stability, and significantly improve the early strength and mid-to-late strength of cement-based materials. The obtained nano-hydrated calcium silicate crystal core with adjustable setting time has small size, high stability, and good early strength effect, and can be directly used to configure concrete or other cement-based materials. The raw materials are easily available, the production process is simple, the synthesis efficiency is high, the reaction conditions are mild, the production cost can be significantly reduced, and the invention is suitable for large-scale promotion and industrial production, showing significant environmental benefits and economic value, and having positive significance for promoting the sustainable development of the construction industry.
[0104] Finally, it should be noted that the various technical features of the above-mentioned embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the various technical features in the above-mentioned embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. The above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A nano calcium silicate hydrate with adjustable setting time, characterized in that: In terms of weight fraction, it includes the following components: 10-40 parts of calcium source, 0.5-3 parts of zinc source, 10-30 parts of silicon source, 5-15 parts of polycarboxylic acid water reducer, 0.5-2 parts of stabilizer, and 100-400 parts of water.
2. A nano calcium silicate hydrate with adjustable setting time according to claim 1, characterized in that: The calcium source is one or more of calcium acetate, calcium nitrate, calcium formate and calcium chloride.
3. A nano calcium silicate hydrate with adjustable setting time according to claim 1, characterized in that: The silicon source is a soluble silicon salt.
4. A nano calcium silicate hydrate with adjustable setting time according to claim 1, characterized in that: The zinc source is one or more of zinc acetate, zinc nitrate, zinc formate and zinc chloride.
5. A nano calcium silicate hydrate with adjustable setting time according to claim 1, characterized in that: The water reducing rate of the polycarboxylic acid-based water reducing agent is ≥35%.
6. A nano calcium silicate hydrate with adjustable setting time according to claim 1, characterized in that: The stabilizer is one or more of block polyether F68, povidone K30, sodium dodecyl sulfate, and sodium dodecyl sulfonate.
7. A method for preparing nano calcium silicate hydrate with adjustable setting time according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Preparation of a dropping solution: Weigh a calcium source, a zinc source and a silicon source, respectively, and dissolve them in water to obtain a calcium source dropping solution, a zinc source dropping solution and a silicon source dropping solution; S2. Preparation of a base liquid: Mixing a polycarboxylate water reducer, a stabilizer and water to obtain a base liquid, and placing it in a cold water bath; S3. Preparation of nano-hydrated calcium silicate: adding the calcium source droplet, zinc source droplet and silicon source droplet to the base liquid, stirring and adjusting the pH value to 10-13 to obtain nano-hydrated calcium silicate.
8. A method for preparing nano calcium silicate hydrate with adjustable setting time according to claim 7, characterized in that: The temperature of the cold water bath in S2 is 5-15°C.
9. A method for preparing nano calcium silicate hydrate with adjustable setting time according to claim 7, characterized in that: S3 The addition time of the calcium source droplet, zinc source droplet and silicon source droplet is 2-3h; the stirring speed is 5000-10000r / min, and the time is 3-5h; the pH value is adjusted by NaOH and HNO3.
10. Use of the nano calcium silicate hydrate with adjustable setting time according to any one of claims 1 to 6 in preparing concrete.
Citation Information
Patent Citations
A hydrated calcium silicate nanocrystal core suspension and its preparation method
CN112010581B